Archives - Joseph M. Doherty, DDS, MPH (Blackwell Synergy, 2000)
Pad M. Turner has retired after more than 33 years from the Centers for Disease Control and Prevention (CDC) effective January 1, 1999. Mr. Turner served in numerous managerial positions in CDC field assignments and at CDC headquarters in Atlanta